2015
DOI: 10.5433/1679-0359.2015v36n5p3421-3430
|View full text |Cite
|
Sign up to set email alerts
|

Citrus pulp in lamb diets: intake, digestibility, and ruminal parameters

Abstract: <p>This study aimed to evaluate the viability of replacing corn meal with citrus pulp (0, 25, 50, 75, and 100 % dry matter of corn meal) by evaluating several nutritional parameters such as intake and digestibility of nutrients, and ruminal fermentation parameters. The diets were formulated to be isoproteic with a roughage:concentrate ratio of 60:40. Five crossbred lambs with an initial average weight of 26.1 ± 1.8 kg were used and distributed in a 5 x 5 Latin Square design. For digestibility of nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It has also been reported by previous researchers that the use of citrus pulp in the diets of dairy animals does not significantly affect milk yield (Belibasakis and Tsirgogianni, 1996;Volanis et al, 2004). On the other hand, Peixoto et al (2015) reported that the use of citrus pulp did not affect volatile fatty acids production or other rumen dynamics. In this case, it is thought that volatile fatty acids, which play an active role in shaping milk yield, are not sufficiently released in the rumen and sufficient resources cannot be sent to the liver to raise blood glucose levels.…”
Section: Performance Findingsmentioning
confidence: 52%
“…It has also been reported by previous researchers that the use of citrus pulp in the diets of dairy animals does not significantly affect milk yield (Belibasakis and Tsirgogianni, 1996;Volanis et al, 2004). On the other hand, Peixoto et al (2015) reported that the use of citrus pulp did not affect volatile fatty acids production or other rumen dynamics. In this case, it is thought that volatile fatty acids, which play an active role in shaping milk yield, are not sufficiently released in the rumen and sufficient resources cannot be sent to the liver to raise blood glucose levels.…”
Section: Performance Findingsmentioning
confidence: 52%
“…Peixoto et al (2015), studying the substitution of corn meal by citrus pulp to sheep (up to 265 g/kg DM) did not find any effect on DM andJOSEMIR S. GONÇALVES et al NEUTRAL DETERGENT-SOLUBLE FIBER FOR SHEEP An Acad Bras Cienc (2022) 94(4) e20200966 12 | 15…”
mentioning
confidence: 99%